Screening of maize rhizobacteria against aflatoxigenic Aspergillus flavus strains in relation to siderophore and HCN production - and A.N. SINGH, A.K. ROY*, N.L. MANDAL (Indian Phytopathology, 2009)
Fifty nine isolates of Aspergillus flavus and thirty nine bacterial isolates were collected from the rhizosphere soil of standing maize crop. Among the bacterial isolates, Bacillus circulans, B. pumilus, B. subtilis, Pseudomonas aeruginosa and P. putida showed antagonistic behaviour against toxigenic Aspergillus flavus in terms of growth and aflatoxin production. On further screening B. pumilus & P. aeruginosa exhibited strong (2+ ) siderophore activity whereas B. circulans and P. putida showed poor (+) and no activity (-) was recorded in case of B. subtilis. Similarly B. pumilus, P. aeruginosa and P. putida were found to have hydrogen cyanide (HCN) production ability whereas B. subtilis and B. circulans failed to produce it. Siderophore and HCN producing bacteria were found to respond against aflatoxin production.